The Bush administrations and Saddam Hussein : deciding on conflict - Hybel, Alex Roberto (Advances in foreign policy analysis., 2006)
The authors present a vital and unsettling analysis of the foreign policy-making processes of the two Bush administrations prior to the attacks on Iraq. In a systematic and thorough comparison, they show how both presidents used historical analogies to evaluate information, relied on instinct to formulate decisions, and drew on moral language to justify their choices. -- Publisher description.